Host response mechanisms to malaria infection: the role of cullin-ring ligases during plasmodium infection - Lopes, Audrey Isabelle Rosado, 1988- (2013)
Tese de mestrado. Biologia (Biologia Celular e Biotecnologia). Universidade de Lisboa, Faculdade de Ciências, 2012